Enhancing Registrar Service Delivery Through an Online Document Request System: A Basis for Process Improvement - Lacorte, Tracy Lei (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study evaluated the registrar document request process of Emilio Aguinaldo College Cavite and proposed a process enhancement framework through a Full Online Document Request System. Anchored on the SERVQUAL model, lean management, and e-service quality theory, the study assessed service quality, workflow inefficiencies, stakeholder concerns, and the feasibility of digital transformation in registrar services. A descriptive and evaluative research design was used, involving 108 respondents composed of 41 students, 56 alumni, and 11 registrar staff. Data were gathered through stakeholder surveys, workflow analysis, SWOT analysis, PESTLE analysis, and multi-criteria decision analysis. Findings revealed major concerns in the current manual and semi-digital process, including long processing time, lack of request tracking, delayed responses, limited accessibility, and untapped digital potential. Long processing time was the most common concern, while 69.09% of respondents supported the implementation of an online system. Real-time tracking and automated notifications were also highly valued by stakeholders. Among the proposed alternatives, the Full Online Document Request System obtained the highest weighted score of 4.50, outperforming the hybrid system and the status quo. The study concluded that a comprehensive online system is the most suitable option for improving efficiency, transparency, accessibility, communication, and stakeholder satisfaction. It recommended actual system deployment, pre-post implementation evaluation, cost-benefit analysis, and long-term monitoring of registrar service performance. The study supports SDG 4, SDG 8, SDG 9, and SDG 16 by strengthening quality education support, employment-related document access, institutional innovation, and transparent service delivery. Its sustainability impact lies in improving institutional efficiency, digital governance, stakeholder access, and long-term administrative service quality.
Keywords: Accessibility; Digital Transformation; E-Service Quality; Full Online Document Request System; Registrar Services; SERVQUAL; Stakeholder Satisfaction; Workflow Improvement